Infecção simples e mista do Cucumber mosaic virus e do Tobacco mosaic virus em diferentes hospedeiras e detecção por RT-PCR multiplex e DAS-ELISA - Facco, Cassiele Uliana (2013)
The objective of this study was to evaluate the symptoms of single and mixed infections in four different hosts induced by an isolate of Cucumber mosaic virus, and by a tomato Tobamovirus isolate from Marialva-PR. We also evaluated the relative concentration of each virus in these hosts, by DAS-ELISA tests. Initially, the species of Tobamovirus was identified using antiserum specific to TMV and ToMV through DAS-ELISA assays, and through RT-PCR with the amplification of approximately 400 bp with primers for TMV. Analysis of the sequence similarity of TMV Marialva-PR with other sequences deposited in GenBank, showed a 100% identity with an isolate originating from Sapopema, Paraná (TMV-PR). Subsequently, simple and mixed inoculations were made with TMV and an isolate of CMV from Catharanthus roseus, whose viral species had been previously determined. Mixed infection of these viruses resulted in the most severe expression of symptoms, demonstrating the synergistic interaction of both viruses. DAS-ELISA tests, such as RT-PCR were efficient for TMV and CMV detection, in single and mixed infections in tomato, pepper, tobacco and Gomphrena globosa. The multiplex RT-PCR protocol was efficient for mixed infection detections, and specific amplifications of each virus demonstrated the applicability of the method for the routine diagnosis for phytosanitary certification of horticultural crops.